Kajian Konsep Arsitektur Bioklimatik Pada Masjid Al Warqa'a, Dubai, Uni Emirat Arab - Ahmad Faisal; Finta Lissimia (Journal of Architectural Design and Development (JAD), 2021)
The mosque is an important public facility for the Muslim community with a function as a place of worship. The comfort of the mosque can affect humility in the process of worship. The bioclimatic architectural approach is a solution that maximizes the benefits of existing conditions through the application of bioclimatic architecture to mosque buildings, and to find out which mosque buildings have a direct influence on aspects of bioclimatic architecture. The purpose of this study is to find out how the application of bioclimatic architecture affects the shape of the Al-Warqa'a mosque. This research method uses descriptive qualitative methods to determine the application of bioclimatic architectural concepts to mosque buildings so that in bioclimatic principles through the layout and shape of the building, the direction and condition of window shading, orientation and color on the walls, building ventilation, material selection. and site landscaping. This study uses secondary data collection methods with variables such as indoor temperature, air flow, and sunlight. Secondary data is a method for surveying data by collecting data from books, journals, archives, and literature from previous research related to the principles of bioclimatic architecture. The results obtained are from 9 bioclimatic principles, there are 2 principles that are not applied to the Al-Warqa'a mosque building, namely terraces and balconies. However, other principles can be applied using adjustments to each of these principles.